EXPERIMENTAL STUDY: THE INFLUENCE OF PAY SCHEME AND PERSONAL VALUE TO BUDGETARY SLACK - sampouw, chrishella erlyn (Jurnal Aplikasi Manajemen, 2018)
This study tested the hypothesis developed by Hobson, et al. (2011), and aims to examine the influence of pay scheme and personal value to budgetary slack. This study uses the experimental method. Participants in this study are accounting study program students who have completed three subject, management control system, budgeting, and management accounting. 35 people participated in the experiment and the data were analyzed using the Kruskal Wallis test. Results of this study indicate that the organization with a truth-inducing compensation scheme less tendency to commit budgetary slack, compared to organizations that implement slack inducing compensation schemes. While judged on the personal value of an employee, a person with high personal value tends not to commit budgetary slack, but the difference is insignificant when compared to a person with low personal value. The results of this study also show that if an organization implements a truth-inducing compensation to someone with high personal value, it will commit the least budgetary slack. Some of the results of this study support the hypothesis developed by Hobson, et al. (2011), but there is one hypothesis that is not supported because the compensation scheme applied in the firm is more dominant in influencing the implementation of budgetary slack.